Performance, Persistence, Benchmarks, Timing Ability and Selectivity of Unit Trusts in Malaysia - Kanteyineza, Norbert (2009)
This study analyses the performance of unit trusts in Malaysia during the period from January 2002 to December 2007. The issues of risk-adjusted performance, benchmarks appropriateness, timing ability and selectivity as well as performance persistence are addressed. We draw on the Capital Asset Pricing Model (CAPM), Arbitrage Pricing Theory (APT) and Jensen’ alpha performance measurement, to examine monthly returns on the sample funds relative to the performance of different benchmarks specifications. Henriksson and Merton (1981) model is used to examine selectivity and timing ability of top performing unit trust managers. Performance persistence of top performing unit trusts is assessed at successive one-year intervals. The results show evidence of general underperformance unit trust Malaysia. This failure is further analyzed in terms of benchmarks appropriateness and the results show that both CAPM and APT benchmarks specification are equally appropriate to assess unit trusts performance. Although, top performing managers have selectivity ability, they do not demonstrate any market timing skills. This study shows also a weak evidence of short-term persistence performance among top performing managers.